The Complexity of Zoonotic Filariasis Episystem and Its Consequences: A Multidisciplinary View. (31st May 2017) - Simón, Fernando; González-Miguel, Javier; Diosdado, Alicia; Gómez, Paula Josefina; Morchón, Rodrigo; Kartashev, Vladimir
Abstract : Vector-borne transmitted helminthic zoonosis affects the health and economy of both developing and developed countries. The concept of episystem includes the set of biological, environmental, and epidemiological elements of these diseases in defined geographic and temporal scales. Dirofilariasis caused by different species of the genus Dirofilaria is a disease affecting domestic and wild canines and felines and man, transmitted by different species of culicid mosquitoes. This complexity is increased because Dirofilaria species harbor intracellular symbiont Wolbachia bacteriae, which play a key role in the embryogenesis and development of dirofilariae and in the inflammatory pathology of the disease. In addition, the vector transmission makes the dirofilariasis susceptible to the influence of the climate and its variations. The present review addresses the analysis of dirofilariasis from the point of view of the episystem, analyzing the complex network of interactions established between biological components, climate, and factors related to human activity, as well as the different problems they pose. The progress of knowledge on human and animal dirofilariasis is largely due to the multidisciplinary approach. Nevertheless, different aspects of the disease need to continue being investigated and cooperation between countries and specialists involved should be intensified.